Congenital Lamellar Icthyosis (Collodion Baby) - Baghel, B (Journal of Nepal Paediatric Society, 2011)
Lamellar ichthyosis, also known as ichthyosis lammellaris and nonbullous congenital ichthyosis, is a rare inherited skin disorder, affecting around 1 in 600,000 people the images of this rare variety of skin disorder has been presented here. DOI: http://dx.doi.org/10.3126/jnps.v31i3.3769 J Nep Paedtr Soc 2011;31(3): 257